Emerging role of a novel small non-coding regulatory RNA: tRNA-derived small RNA - Fangfang Jin; Zhigang Guo (ExRNA)
Abstract The discovery of small non-coding RNAs, such as miRNA and piRNA, has dramatically changed our understanding of the role RNA plays in organisms. Recent studies show that a novel small non-coding RNA generated from cleavage of tRNA or pre-tRNA, called tRNA-derived small RNA (tsRNA), serves as a new regulator of gene expression. tsRNA has been determined participate in regulating some specific physiological and pathological processes. Although knowledge regarding the biological roles of miRNA and piRNA is expanding, whether tsRNAs play similar roles remains poorly understood. Here, we review the current knowledge regarding the mechanisms of action and biological functions of tsRNAs in intracellular, extracellular and intergenerational inheritance, and highlight the potential application of tsRNAs in human diseases, and present the current problems and future research directions.